Implant-supported titanium framework: photoelastic analysis before and after spark erosion procedure - Cariello, Mauricio Pompeu (2015)
Aim: This study used a photoelastic analysis to evaluate the passive fit of titanium cast laser welding frameworks before and after spark erosion procedure. Methods: A stainless steel cast was used in order to reproduce a human mandible. Five Multi-Unit abutment analogs were attached to this cast and 6 frameworks were produced in commercial pure titanium. The cast was molded and a photoelastic matrix was produced incorporating 5 dental implants with Multi-Unit abutments. All samples were subjected to a laser welding. The precision of adjustments within a range of 0.5 µm was evaluated under microscope observation. The best fitted framework was selected and subjected to a photoelastic analysis (Group I). The tightening of the screws was in 3 predetermined sequences (1,2,3,4,5/ 5,4,3,2,1/ 3,2,4,1,5). Then the same framework was subjected to a refinement by spark erosion technique (Group II) and evaluated by photoelastic analysis. Results: The sequence (3,2,4,1,5) achieved better results in both groups. A larger number of fringes were observed around the median implants in all sequences in both groups. Conclusions: The titanium cast laser welded frameworks processes associated with spark erosion procedure improves significantly the marginal framework adaptation and is effective for its passive fit.